Review of renal anastomosing hemangioma with focus on clinical and pathological aspects - Kuroda, Naoto; Ohe, Chisato; Deepika, Sirohi; Yorita, Kenji; Mikami, Shuji; Furuya, Mitsuko; Nagashima, Yoji; Hes, Ondrej; Agaimy, Abbas; Michal, Michal; Amin, Mahul B. (Polish Journal of Pathology, 2016)
Renal anastomosing hemangiomas (RAH) has been recently proposed as a new entity. In this article, we summarize the clinicopathologic features of this tumor. RAH usually develops on a background of end-stage renal disease. Macroscopically, tumors are well-defined and their cut surface shows mahogany brown spongy tissue with epicenter in the renal medulla. Tumors are usually small, but larger lesions are reported. On microscopic examination, the tumor consists of sinusoid-like vascular channels lined by cuboidal endothelial cells with occasional hobnail-like appearance of endothelial cells closely mimicking splenic sinusoids. Eosinophilic hyaline globules may be present in the cytoplasm of neoplastic endothelial cells. Extramedullary hematopoiesis containing erythroid precursor and megakaryocytes may be present in the vascular lumens. Immunohistochemically, endothelial cells are positive for CD31 and CD34, but negative for D2-40, GLUT-1 and HHV8. The surrounding stroma around endothelial cells demonstrates positivity for ? smooth muscle action. To date, there are no studies on molecular genetic aspects of RAH. This tumor is indolent based on site and size of the lesion, partial or nephrectomy is sufficient as a therapeutic modality.
EVALuna2:6827